2019
DOI: 10.1017/cts.2019.417
|View full text |Cite
|
Sign up to set email alerts
|

Public feedback on a proposed statewide virtual translational research community

Abstract: Introduction: Researchers have explored using the internet and social media to recruit participants to specific research projects. Less systematic work has been done to inform the engagement of large populations in virtual communities to advance clinical and translational science. We report on our first step to use social media to engage Minnesota residents by studying the willingness of participants to engage in a virtual (Facebook) community about the concepts of health and health-related research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Content included both noninteractive postings (e.g., research articles related to health research) and interactive postings/events (e.g., live interviews with researchers). Content for health topics was prioritized based on preferences suggested in our prior survey [20], including mental health, health and wellness (e.g., nutrition, physical activity), chronic diseases (e.g., cardiovascular disease), and immunology/infectious diseases. The onset of COVID-19 changed some of the posting plans for MN Research Link.…”
Section: Mn Research Link Facebook Contentmentioning
confidence: 99%
See 3 more Smart Citations
“…Content included both noninteractive postings (e.g., research articles related to health research) and interactive postings/events (e.g., live interviews with researchers). Content for health topics was prioritized based on preferences suggested in our prior survey [20], including mental health, health and wellness (e.g., nutrition, physical activity), chronic diseases (e.g., cardiovascular disease), and immunology/infectious diseases. The onset of COVID-19 changed some of the posting plans for MN Research Link.…”
Section: Mn Research Link Facebook Contentmentioning
confidence: 99%
“…Another topic receiving attention in the news media during the program evaluation period was the health effects of vaping/electronic cigarette use; therefore, content was created to address this topic. Our prior survey [20] indicated that individuals wanted credible, accurate, and reliable health information and provision of research findings, as well as information about participating in research. For health topics, findings from research studies including research articles were included with a prioritization of research articles and studies with a connection to the Minnesota community.…”
Section: Mn Research Link Facebook Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…We focused on these two health outcomes, because mental health and obesity were identified as the top two community health priorities from 2014 to 2016 in all three counties [4][5][6][7]. In addition, a survey involving a convenience sample of 418 community members statewide in Minnesota (10% rural residence) revealed that mental health and wellness (e.g., obesity and physical activity) were reported as top health needs [8]. Consistent with a bi-directional approach to community engagement [9], we seek to understand the influence of rural-urban geographic location on disparities in health outcomes identified as important to our local communities.…”
Section: Introductionmentioning
confidence: 99%